Analisis Pengaruh Customer Experience, Customer Value, Dan Ease Of Use Terhadap Pembelian Ulang Melalui Toko Online Di Shopee - Wahyu Utama, Juventius; Anang Tri Wahyono (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This research is intended to discuss the effect of consumer experience, customer value, and ease of use on repurchasing as the research object for product buyers at the Shopee online store. This study used a sample of 100 respondents, and used an accidental sampling technique, by distributing questionnaires to respondents who had purchased products at the Shopee online store at least 2 times. Analysis of the data used in this study is the validity test, reliability test and linear regression testing with the help of the SPSS 21 program. The results of this study indicate that customer experience, customer value and ease of use have a positive and significant effect on repeat purchases at the Shopee online store.